ABOUT THE ORGANIZATION OF KNOWLEDGE AS A CONTROL FEEDBACK IN THE COMPUTER MATHEMATICS OF EDUCATIONAL APPOINTMENTS (Journal of Information Technologies in Education (ITE), 2014)
This article describes system of computer mathematics for educational purposes with intellectual features that focus on supporting of practical activity of users. Also submitted the control of knowledge as a form of feedback in information support system of learning process.
Keywords: Software systems for educational purposes; the model of learning; e-teaching materials; control of knowledge; tests